Nebulized mRNA‐Encoded Antibodies Protect Hamsters from SARS‐CoV‐2 Infection. Issue 34 (31st October 2022) - Vanover, Daryll; Zurla, Chiara; Peck, Hannah E.; Orr‐Burks, Nichole; Joo, Jae Yeon; Murray, Jackelyn; Holladay, Nathan; Hobbs, Ryan A.; Jung, Younghun; Chaves, Lorena C. S.; Rotolo, Laura; Lifland, Aaron W.; et al.
Abstract: Despite the success of severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) vaccines, there remains a clear need for new classes of preventatives for respiratory viral infections due to vaccine hesitancy, lack of sterilizing immunity, and for at‐risk patient populations, including the immunocompromised. While many neutralizing antibodies have been identified, and several approved, to treat COVID‐19, systemic delivery, large doses, and high costs have the potential to limit their widespread use, especially in low‐ and middle‐income countries. To use these antibodies more efficiently, an inhalable formulation is developed that allows for the expression of mRNA‐encoded, membrane‐anchored neutralizing antibodies in the lung to mitigate SARS‐CoV‐2 infections. First, the ability of mRNA‐encoded, membrane‐anchored, anti‐SARS‐CoV‐2 antibodies to prevent infections in vitro is demonstrated. Next, it is demonstrated that nebulizer‐based delivery of these mRNA‐expressed neutralizing antibodies potently abrogates disease in the hamster model. Overall, these results support the use of nebulizer‐based mRNA expression of neutralizing antibodies as a new paradigm for mitigating respiratory virus infections. Abstract : Despite the success of vaccination, severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) remains an ongoing threat worldwide. Monoclonal antibody therapies have proven useful but are expensive and require high systemic doses. This study reports mRNA‐expressed membrane‐anchored antibodies along with an inhalable polymeric nanoparticle formulation that prevent SARS‐CoV‐2 infection in the stringent hamster model.